The LGBTQ Supportive Environments Inventory: Methods for quantifying supportive environments for LGBTQ youths. Issue 3 (3rd July 2019) - Gower, Amy L.; Saewyc, Elizabeth M.; Corliss, Heather L.; Kne, Len; Erickson, Darin J.; Eisenberg, Marla E.
Abstract: The social environment in which lesbian, gay, bisexual, transgender, and queer (LGBTQ) youths live influences health and well-being. We describe the development of the LGBTQ Supportive Environments Inventory (LGBTQ SEI), designed to quantify the LGBTQ-inclusiveness of social environments in the United States and Canada. We quantify aspects of the social environment including: (1) presence/quality of LGBTQ youth-serving organizations; (2) LGBTQ-inclusive community resources; and (3) socioeconomic and political environment. Using geographic information systems (GIS) tools, we aggregated data to buffers around 397 schools in three regions. The LGBTQ SEI can be used to assess the role of the social environment in reducing health disparities for LGBTQ youths.